Divine Presence and Absence - Berlejung, Angelika (The Oxford handbook of ritual and worship in the Hebrew Bible, 2020)
The topic of divine presence and absence is embedded in the theological debate about the communication between human beings and their gods. Intact communication and divine presence belong together, as well as disturbed communication and divine absence. The interpretation and construction of their own history (of the individual, as well as of the collective) as result of the interplay between divine presence/blessing or divine absence/punishment was a basic pattern. Different literary traditions in the Old Testament attest how the theology of the presence of YHWH was in pre-exilic times a local kind of play of traditional ancient Near Eastern conceptions and mainly connected to Zion. However, after the fall of Jerusalem (perhaps already Samaria), the theology of YHWH’s presence underwent various processes of mobilization, spiritualization, and abstraction. The rebuilding of the Second Temple in Jerusalem was a new impulse for the discussion about the mode(s) of divine presence. Several concepts found their way into the canon which are sketched in this contribution.